Stroke phase differences in the linear relationship between swimming velocity and vertical body position during front crawl - Washino, S.; Murai, A.; Kadi, T.; Mankyu, H.; Yoshitake, Y. (Sports Biomechanics, 2025)
We aimed to investigate whether a linear relationship exists between swimming velocity and vertical body position for each stroke phase in front crawl, and to determine whether there are differences in the velocity effect among the stroke phases. Eleven male swimmers performed a 15 m front crawl at various swimming velocities. The whole-body centre of mass (CoM) was estimated from individual digital human models using inverse kinematics. The horizontal CoM velocity and vertical CoM position from the water surface were calculated for one stroke cycle and divided into five stroke phases: entry, pull, push, release, and recovery. Linear mixed-effects model analysis revealed a positive trend between the mean swimming velocity and the mean vertical CoM position for each stroke phase (p < 0.001 for all phases). The interaction term between stroke phase and swimming velocity was significant (p < 0.001), and the slopes of the propulsive phases (pull and push) were larger than those of the non-propulsive phases (entry, release, and recovery) (p < 0.001). These findings provide practical implications that vertical body position can be evaluated independently of the stroke phase while considering velocity effects, and that focusing on propulsive phases allows easier detection of vertical body position changes.